Selección de alternativa óptima de la presa Toma Grande aplicando el método de Análisis Jerárquico - Arbaiza Ocrospoma, Hulinho Yordy (2023)
In this research work, the analysis and selection of the optimal type of the Toma Grande Dam is applied by using the analytical hierarchical process (AHP), considering 4 dam alternatives (CFRD, RCC, Gravity Concrete, Earth and Enrocado). For the application of the method, the factors that influence the selection of the type of dam were identified, which were called Subcriteria. These were grouped into 8 more representative groups, by means of a hierarchy tree, which were called Criteria (topography and geology, availability of materials, related works, dam safety, river diversion system, construction procedure, construction time and cost of work). The data for the Criteria were obtained from the basic engineering studies and a paired comparison matrix was constructed to obtain the weightings by comparing each of the Criteria with each other. The consistency relationship of the selection criteria was established, in order to then construct the pairwise comparison matrix for the selection of the type of dam according to the Criteria. The results of the analysis indicate that the Gravity Concrete dam as the optimal alternative dam type, with a weighting of 40%.